2009
DOI: 10.1097/jom.0b013e3181a2ca20
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Study Update of Ethylene Oxide Workers in Chemical Manufacturing: A 15 Year Update

Abstract: Despite the relatively high EO exposures in the past and extensive mortality follow-up, the cause specific mortality rates are comparable with those of the general US population. The Standardized Mortality Ratio analyses and the proportional hazards modeling for all cause mortality, leukemia and lymphoid malignancies mortality do not indicate exposure related effects in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 16 publications
1
22
0
1
Order By: Relevance
“…Consistent with the above finding were the findings of Jensen et al, (2001); Saarni et al, (2001);Olaf et al, (2006);and Hoever and Hansen (2005) who found occupational health and safety hazards in the shipping industry as well as Takeishi (2009);and Swaen et al (2009) who also revealed same levels of health and safety hazards in the manufacturing industry. These findings confirm that both industries are exposed to occupational health and safety hazards.…”
Section: Discussion Of Findingssupporting
confidence: 80%
See 1 more Smart Citation
“…Consistent with the above finding were the findings of Jensen et al, (2001); Saarni et al, (2001);Olaf et al, (2006);and Hoever and Hansen (2005) who found occupational health and safety hazards in the shipping industry as well as Takeishi (2009);and Swaen et al (2009) who also revealed same levels of health and safety hazards in the manufacturing industry. These findings confirm that both industries are exposed to occupational health and safety hazards.…”
Section: Discussion Of Findingssupporting
confidence: 80%
“…These studies found occupational hazards such as oral and dental hazards, back pains; body pains, high temperatures, HIV infections, violence, slips and fall by seafarers. Besides, researchers such as Takeishi (2009), Swaen et al, (2009), Sallmen et al, (2008, and Lombardi et al, (2005) have also found occupational health and safety hazards such as noise-related operational hazards, chemical hazards, and eye injuries in the manufacturing industry. Further, few studies have also investigated employee health and safety attitudes in both industries and have found several attitudinal and behavioural tendencies of employees and managers toward employee health and safety practices.…”
Section: Employee Health and Safety Practices In The Shipping And Manmentioning
confidence: 99%
“…A cohort study of men exposed to ethylene oxide (a carcinogen linked to breast cancer in women) did not report the occurrence of breast cancer in the studied workers [ 212 ]. A large study carried out in the Nordic countries reported higher than expected standardized incidence rates among journalists, cooks, stewards, printers, artistic workers, and building caretakers [ 106 ]; the authors underline that a common characteristic of these occupations is that they usually include shift work, which has been associated with increased breast cancer risk in women [ 79 ].…”
Section: Various Occupationsmentioning
confidence: 76%
“…26 Although properly-designed community-based casecontrol studies such as the one we conducted may have some advantages over cohort studies, caution is required in interpreting the analysis by subgroups. Random variation related to the small prevalence of the exposed might account for some positive results.…”
Section: Discussionmentioning
confidence: 99%